Stylistic Study On The Novel “Gadis Pantai” Pramoedya Ananta Toer's Work And Its Relevance As Reading Material In High School - Etika Suri Handayani; Erikson Saragih; Rosliani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the stylistic study of the novel “Gadis Pantai” by Pramoedya Ananta Toer and its relevance as reading material in high school. The method used in this research is the descriptive method. The research data is in the form of words, sentences, and expressions described to explain stylistic studies in the novel “Gadis Pantai” by Pramoedya Ananta Toer, namely, diction, the figure of speech, images, and their relevance as reading material in high school. The results obtained in this study are the use of diction, namely the connotative word and Javanese vocabulary, there is the use of the figure of speech, namely comparison, contradiction, affirmation, and satire. Controversy figures consist of simile figures, metaphorical figures, personification figures, sinekdoke figures, hyperbolic figures, antonomasia figures, and eponymous figures. The affirmation language consists of ellipsis and repitition figure. The satire language consists of the irony figure and the antifrasis figure. There is the use of imagery, namely hearing images, visual images, olfactory images, tactile images, taste images, and intellectual imagery, and the novel “Gadis Pantai” by Pramoedya Ananta Toer is very relevant to be used as reading material, this is because the stories in the novel “Gadis Pantai” contain many messages morals, one of which is so that we can respect others, and do not look at other people from their caste and position. By reading this novel “Gadis Pantai”, can add a source of inspiration and the many uses of stylistic studies in the novel “Gadis Pantai” can increase vocabulary for students. This vocabulary can be used by students when writing a fictional story such as a novel.